The Effect of Using Quizwhizzer Application on Learning Outcomes of Grade VII Junior High School Students on Pythagoras Theorem Material - Hazim Saputra Filia Reza; Intan Maharani; Agitha Amy Meiwari; Reasty Amanda; Fridgo Tasman (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2024)
Mathematics is very concerned with understanding concepts in the process of working. There are still many students who are constrained in understanding the concept of a material because learning is a little monotonous and lacks dance, this has an impact on the low learning outcomes of students in mathematics. This study was conducted to see whether the QuizWhizzher application media could have a positive influence on student learning. This research was conducted in class VII.6 SMP IT Madani Islamic School Payakumbuh with the type of research that is a combination of quantitative and qualitative. Quantitative data is obtained from students' learning outcomes, starting from the pre-test and post-test. Qualitative data is obtained by describing the data obtained quantitatively and also explaining whether there is a positive influence or not. The results of this study indicate an increase in student learning outcomes in the Pythagorean Theorem material with an average of 81.67, so it can be said that QuizWhizzer is effectively used to improve student learning outcomes.